Políticas públicas para fortalecer la comprensión lectora: un análisis comparativo sobre Colombia, Ecuador, México y Venezuela: Public policies to strengthen reading comprehension: a comparative analysis of Colombia, Ecuador, Mexico and Venezuela - Aguilera Carvajal, Javier José (Encuentro Educacional, 2024)
Despite the intense flow of information that can be accessed today, reading comprehension is in a critical situation in different societies, which makes it necessary to implement public policies that comprehensively address this problem. In the educational field, these interventions involve different actors, including directors and teachers, who are aware of student shortcomings and are the ones who, from their pedagogical management, implement and lead the necessary actions to reorient educational processes, directing them towards the achievement of goals and the attainment of academic objectives that, over time, become increasingly closer to global standards of educational quality. In this sense, the objective of this research was to comparatively analyze some of the public reading policies of Colombia, Ecuador, Mexico and Venezuela. To do so, the study was based on the postulates of Machado, Magalón and Rodríguez (2019), Escalante (2019), Cassany (2004), among others. A documentary review was conducted of the educational policies implemented by government entities and a look at the most recent results of evaluations by international organizations that are responsible for quantifying progress in school matters, particularly reading comprehension. The results showed that these policies implemented, although they have required significant administrative, financial and logistical efforts, have not achieved significant progress in strengthening reading comprehension in students.